It's the worry that got him in the end: the importance in treating melanoma holistically and dealing with fear of recurrence. (1st April 2020) - Thompson, A.R.; Cockayne, S.
Abstract: Linked Article: Dieng et al. Br J Dermatol 2020; 182 :860–868 .